International Law Issues of Cyber Defense - A. Yeremyan; L. Yeremyan (Московский журнал международного права)
INTRODUCTION. The world has many times faced cardinal changes triggered by technological development. Creation of the Internet and the emergence of the artiﬁcial intelligence have become the major trend of the ongoing changes with the signiﬁ-cant potential to aﬀect all spheres of live, including the military aﬀairs and the geopolitical phenomena in general. In this paper, in particular, we discuss the opportunities and challenges of the rapid technological development in the defense sector in the context of globalization. The pace and the nature of changes in defense dictate the necessity to analyze the current and future challenges of our digitized age in search of adequate and timely legal and strategic practical solutions. Cyber means of warfare are the weapons of the present. Over the past decades, cyber means of warfare have been frequently used against states in the context of international and non-international armed conﬂicts, as well as outside of such context. Thus, the fundamental scientiﬁc questions that arise are the following: a) are the current legal regulations at international and national levels suﬃcient to address all the challenges caused by the spillover of armed conﬂicts into the virtual domain and by the future advancement of cyber weapons, and b) are the current cyber weapons or those of the future capable of changing the nature of “war” described by General Carl von Clausewitz yet in the 19th century as a violent method of forcing its political will by one party of the conﬂict to the other. We have analyzed the above-mentioned questions in the light of the cyber weapons, which already exist and are being used for military purposes, in the light of possible advancement of cyber weapons and integration of AI into them, as well as in the light of the Big Data management. We have reﬂected on the dangers, which the smart and entirely data driven world would face, from legal and geopolitical perspectives, through the several possible scenarios of development, emphasizing, in particular, the probable military (defense) aspect of data management. While most frequently the speciﬁc problems of application of International Law to the traditional cyber warfare situations become subject for academic debates and discussions, we stress the necessity to also analyze the legal and practical implications of further advancement of cyber weapons, as well as the necessity to consider the role of Big Data management in changing the nature of war and, consequently, also the applicable legal solutions.MATERIALS AND METHODS. The works of academics and international scholars in the ﬁeld of international law and, speciﬁcally, international humanitarian law, and military theorists, as well as international treaties, commentaries to international treaties, and national cyber defense and cyber security strategies comprise the theoretical basis for the current paper. The research has been conducted via general and speciﬁc scientiﬁc methods of cognition, in particular the dialectical method, comparative legal method, method of interpretation, as well as methods of deduction, induction, analysis, synthesis, and others.RESEARCH RESULTS. The ongoing changes taking place in the world have resulted in a situation, when cyber domain is considered one of the traditional war domains. In this context the international community is now debating more ﬂexible interpretations of international legal regulations in order to most eﬃciently address the new reality. It is also important that states at national level undertake measures to timely and adequately address the challenges already created and those that potentially may take place as a result of the globalization along with the rapid evolution of the cyber technologies and their military use. In the current article we conclude that the categories of the present generation of cyber weapons are lawful. However, the future developments in cyber weapon technologies, as well as the possible quasi-military implications of Big Data management raise many theoretical and practical questions deserving attention. The eﬀorts of the international community and individual states in the ﬁeld of legal regulation of cyber technologies should be directed toward creating guarantees that the products of the technological development are used for the beneﬁt of humankind. As one of such measures The Authors indicate national cyber security and cyber defense strategies, which according to the Authors, should be elaborated giving due consideration to the possible future developments.DISCUSSION AND CONCLUSIONS. In this paper we analyze the peculiar features of evolution of the world in the 21st century and argue that wars are not static and autonomous phenomena isolated from the global context and all the changes taking place in the world. In particular, we address one of the most popular debates among the scholars in the ﬁeld of military aﬀairs concerning the issue whether the nature of war has changed or will change overtime, referring to Carl von Clausewitz’s thoughts. With regard to the current generation of cyber weapons, we conclude that even if they might prima facie seem to be inherently indiscriminate (such as, for example, nuclear weapons) in reality cyber weapons are not per se indiscriminate, but rather are weapons with a very high potential of being used indiscriminately or in violation of the principle of discrimination. However, the high potential of indiscriminate use of cyber weapons does not outlaw the cyber weapons as such. We also agree with the widely accepted opinion that the cyber weapons, which are currently used, are sufﬁciently regulated by the International Law. At the same time, the future tendencies for advancement and improvement of military cyber technologies, inter alia, via integration of artiﬁcial intelligence, may seriously call into question the possibility of their application in compliance with the international legal regulations. Finally, the possible scenarios of advancement of Big Data management have led us to the conclusion that big data management per se has the potential of being used as a weapon with less lethal or even non-lethal consequences, however equally eﬀective in enforcing one’s policy as the traditional weapons or potentially kinetic cyber-weapons. If big data analysis at its current stage of development does not produce very accurate predictions, the well-distributed and structured informational ﬂow in the cyber domain is capable of inﬂuencing and manipulating behaviours. In such case if Big data monopoly (including both: hardware and soﬅware) vests in one of several actor, it could drastically change the nature of war by making the element of violence redundant and consequently alter the geopolitical balance. One of the measures for early response to future challenges, in our opinion, could be through reﬂecting on lex ferenda in cyber security and cyber defence national strategies. From the analysis of the content of diﬀerent strategies we could conclude that most states acknowledge cyberspace as a military domain like land, air or maritime, analyse the main speciﬁc characteristics of current generation of cyber weapons, and set state objectives and action plan for cyber oﬀense, cyber defense and cyber deterrence respectively. While the future advancement of cyber means of warfare and the quasi-military dimension of the big data management seem to be overlooked by states in general.